Retrospective study on the endovascular embolization for traumatic carotid cavernous fistula - 张立朝 许民辉 杨东虹 邹咏文 张云东 (Chinese journal of traumatology, 2010)
Objective： To retrospectively analyze 95 cases of traumatic carotid cavernous fistula treated by endovascular embolization. Methods： From January 1994 to December 2008, 95 patients with traumatic carotid cavernous fistula were treated in our hospital. All patients received selective cerebral angiography through femoral artery catheterization. Accordingly, 89 cases were treated by detachable balloon embolization, 5 by platinum microcoils and 1 by coveredstem, respectively. Results： In the study, 61 cases achieved successful balloon embolization at the first time. Fifty-six cases had multiple balloons due to the big fistula. Nine cases received balloon embolization twice. But among the 5 patients treated with platinum microcoils, one developed slight brainstem ischemia. After operation the patient had herniparesis and swallow difficulty, but gradually recovered 3 months later. No neurological deficits were observed in other cases. All the cases recovered. Eighty-five cases were followed up for 1-15 years and no recurrence was found. Conclusions： The endovascular embolization for traumatic carotid cavernous fistula is minimally invasive, safe, effective and reliable. The detachable balloon embolization is the first choice in the treatment of TCCF.